Relaxant effect of 7-ethoxy-4-methyl-2H-chromen-2-one by calcium channel blockade: computational and ex vivo studies - Amanda Sánchez-Recillas, Gabriel Navarrete-Vázquez, César Millán-Pacheco, Berenice Aguilar-Guadarrama, Rolffy Ortiz-Andrade, SamuelEstrada-Soto (Journal of Applied Pharmaceutical Science, 2014)
Current work was conducted in order to determine the underlying mode of relaxant action of 7-ethoxy-4-methyl-2H-chromen-2-one (1), a coumarin obtained by semisynthesis from umbelliferone (2), with significant relaxant effect in a concentration-dependent manner on tracheal rat rings pre-contracted with carbachol (1 µM). In a previous study it was demonstrated that compound 1 and 2 showed significant relaxant effect, being 1 the most active compound (Emax= 100% and EC50= 83 µM) even more active than theophylline [an unspecific phosphodiesterases (PDE’s) inhibitor] used as positive control. Moreover, pretreatment with 1 significantly shifted to the right the carbachol-induced contraction. On the other hand, compound 1 (83 µM) produces significant (100%) relaxant effect on the contraction induced by KCl (80 mM) and the CaCl2-induced contraction was significantly reduced by the coumarin 1 as nifedipine does (a L-type calcium channel blocker), used as positive control. Indomethacin (10 µM, unspecific COX inhibitor) significantly reduced 1-relaxation. Meanwhile, in the presence of isoproterenol (a β-adrenergic agonist), and K+ channel blockers glibenclamide (10 µM) and 2-AP (100 µM) the relaxant curve was not modified. Compound 1 was docked on an outer cavity located on the extracellular side of the human L-type calcium channel model (affinity energy -6.8 kcal/mol). However, compound 1 was also found on the same location as nifedipine with the same affinity energy (-6.3 kcal/mol) as previously described. Both conformations were stabilized by aliphatic interactions on both binding sites, primordially by a π-π interaction between FIVS6.7 and aromatic rings from compound 1. In conclusion, 7-ethoxy-4-methyl-2H-chromen-2-one (1) induces a significant relaxant action on rat trachea rings, through L-type calcium channel blockade and, as a second mechanism of action, by a possible intracellular cyclic AMP increasing.
Keywords: Coumarin, docking, 7-ethoxy-4-methyl-2H-chromen-2-one, umbelliferone, calcium channel, trachea.